2023
DOI: 10.1038/s41598-023-30299-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in immune tissues of adult chickens after embryo stimulation with bioactive substances

Abstract: The microbiota has a profound impact on the host organisms. The interaction between the host and its microbiota has an epigenetic mode of action. In poultry species, gastrointestinal microbiota might be stimulated before hatching. This stimulation with bioactive substances has a broad spectrum and long-term effects. This study aimed to examine the role of miRNA expression stimulated by host-microbiota interaction via administering a bioactive substance at the stage of embryonic development. This paper is a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Studies reveal a correlational relationship between bacteria, SCFAs and miRNAs regulating inflammatory processes in the intestine as well as in other organs ( 263 267 ). The gut microbiota was also shown to downregulate proinflammatory cytokines and the transport of proinflammatory bacterial peptides by peptide transporter 1 (PepT1) via miRNA upregulation ( 268 270 ).…”
Section: Scfa-epigenetic Regulationmentioning
confidence: 99%
“…Studies reveal a correlational relationship between bacteria, SCFAs and miRNAs regulating inflammatory processes in the intestine as well as in other organs ( 263 267 ). The gut microbiota was also shown to downregulate proinflammatory cytokines and the transport of proinflammatory bacterial peptides by peptide transporter 1 (PepT1) via miRNA upregulation ( 268 270 ).…”
Section: Scfa-epigenetic Regulationmentioning
confidence: 99%
“…Different studies showed that regular dietary supplementation of XOS can effectively feed the gut microbiome and change the gut metabolite composition [12,13], but the effects of in ovo feeding of XOS are yet to be thoroughly understood. Other studies found that in ovo stimulation with bioactive compounds can stimulate the gut microbiota before hatch and lead to regulating cecal microbiota, shortchain fatty acids (SCFA) production, and immunity in adult broilers [10,14,15]. However, there is a scarcity of information regarding the effect of in ovo XOS feeding on inducing changes in post-hatch broiler chickens.…”
Section: Introductionmentioning
confidence: 99%